Pengaruh Level Minyak Kelapa Murni dalam Pengencer Air Kelapa Muda Terhadap Kualitas Spermatozoa Babi Landrace - Woda, Agustio Sarcyano Sola; Kune, Petrus; Marawali, Aloysius (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aimed to examine the addition of various levels of virgin coconut oil (VCO) in young coconut water-egg yolk (YCW-EY) diluent on the quality of landrace boar spermatozoa. Semen was collected once a week using the massage method from landrace boars that have reached sexual maturity with healthy conditions. This study was experimental with a completely randomized design consisting of five treatments and five replicates. The treatments consisted of young coconut water (YCW 80%) and egg yolk (EY 20%) added with virgin coconut oil (VCO) with levels: 0% (P0), 2% (P1), 4% (P2), 6% (P3) and 8% (P4). The diluted semen was stored in a cool box at 15-20ºC and evaluated every 8 hours for motility, viability, abnormality and survival of spermatozoa up to a minimum motility of 40%. The results of this study showed that semen diluted using YCW-EY in treatment P4 (VCO 8%) had higher quality (P<0.05) compared to other treatments, namely motility reached (43.00±7.59%), viability (49.20±7.59%), abnormality (4.56±2.36%) and survival (25.42±2.78 hours). It was concluded that the addition of 8% VCO to YCW-EY diluent was effective in maintaining the quality of landrace boar spermatozoa.